Consequence of Ballistic Training and Plyometric Training on Muscular Strength and Vital Capacity among College Men Football Players - Dr. A. Praveen (International Journal of Advanced Science and Technology, 2020)
Throughout this study 45 men, football players who complete the inter-college level players from the University of Pondicherry and their age group between 18 and 22 must participate in this analysis which is made to investigate the effects of ballistic training and plyometric training on muscle strength and vital ability among college men footballers. Players are split into three equal classes of 15 experimental group subjects – I ballistic training group, experimental group II plyometric training group and no experimental treatment was provided by Control group. The experimental group I and II had adopted the prestige strategy with 3 alternating days in a week for 12 weeks. At pre-test and post-test, the data recovery process is achieved by muscle strength with Kraus Webber back strength check and vital ability with web spirometer. ANCOVA must analyze the collected data to assess the variations. The post hoc study by Scheffe was used to analyze the disparity between classes and test conditions. The level of confidence was set at a scale of 0.05. Report of the analysis indicates ballistic testing and as opposed to the control group, plyometric preparation provides good muscle power and control group.